Serum and expression profiles of glucose-dependent insulinotropic polypeptide in correlation with cardiometabolic risk factors among patients with systemic lupus erythematosus - Nearmeen M Rashad; Reem M Allam; Amany M Ebaid; Mohammed S Yousef; Maha A Fathy (SpringerOpen, 2019)
Background Premature atherosclerosis has been recognized as a major co-morbid condition in systemic lupus erythematosus (SLE). Glucose-dependent insulinotropic polypeptide (GIP) is closely related to cardiovascular (CV) risk factors. We aimed to evaluate GIP expression level in SLE and to explore the possible associations of GIP expression profile with carotid intima-media thickness and insulin resistance (IR). Patients and methods A cross-sectional controlled study was conducted, comprising 170 patients with SLE and 120 controls. GIP expression level was measured by multiplex polymerase chain reaction. The carotid intimamedia thickness was measured. Serum GIP levels, homeostasis model assessments (HOMA-IR and HOMA-b), fibrinogen, and homocysteine were measured. Results In the patients with SLE with IR, there were significantly higher values of serum GIP (37.99±13.64) compared with patients with SLE without IR (24.61±10.74), as well as the control group (21.7±3.46). In addition, there were significant positive correlations between GIP serum level and cardiovascular risks. Regarding GIP gene expression levels, there were significantly lower levels of GIP gene expression in patients with SLE with IR (1.29±0.72) compared with patients with SLE without IR (2.43±0.61) as well as the control group. Receiver operating characteristic analysis revealed that the diagnostic power of GIP expression was stronger than GIP serum levels in differentiating SLE from control. In conclusion, in the SLE group, there were lower GIP expression and higher serum levels than control, especially in IR subgroup. GIP expression and serum levels were associated with cardiovascular disease pathogenesis and progression.